2021
DOI: 10.18632/aging.202559
|View full text |Cite
|
Sign up to set email alerts
|

Infertility network and hub genes for nonobstructive azoospermia utilizing integrative analysis

Abstract: Non-obstructive azoospermia (NOA) is the most severe form of male infertility owing to the absence of sperm during ejaculation as a result of failed spermatogenesis. The molecular mechanisms of NOA have not been well studied. Here, we revealed the dysregulated differentially expressed genes in NOA and related signaling pathways or biological processes. Cluster features of biological processes include spermatogenesis, fertilization, cilium movement, penetration of zona pellucida, sperm chromatin condensation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Meanwhile, the interested genes were not restricted to one gene or several genes, the researchers could detect a gene family (such as Interleukins) or a series of function-related genes (such as inflammatory cytokine receptors) in scRNA-seq data 142 , which could give researchers a view on macroscale. Moreover, an updated usage of this process was to not only show the type of cells that a certain gene was expressed in, but also show its transcriptional changes during spermatogenesis 143 or among different pathological groups 127 , 144 . A good example came from He et al's work 127 , in which they identified four interested genes ( KIF2C , MRPS2 , RPS15 and TSFM ), and then based on human scRNA-seq data of both KS testes and normal testes, they showed that KIF2C were downregulated while RPS15 were upregulated in KS testes.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the interested genes were not restricted to one gene or several genes, the researchers could detect a gene family (such as Interleukins) or a series of function-related genes (such as inflammatory cytokine receptors) in scRNA-seq data 142 , which could give researchers a view on macroscale. Moreover, an updated usage of this process was to not only show the type of cells that a certain gene was expressed in, but also show its transcriptional changes during spermatogenesis 143 or among different pathological groups 127 , 144 . A good example came from He et al's work 127 , in which they identified four interested genes ( KIF2C , MRPS2 , RPS15 and TSFM ), and then based on human scRNA-seq data of both KS testes and normal testes, they showed that KIF2C were downregulated while RPS15 were upregulated in KS testes.…”
Section: Resultsmentioning
confidence: 99%
“…It seems that SNP analysis has also shown a strong association between sperm chromatin structure and infertility, and some genes have the potential to become biomarkers. Han et al in 2021 showed that CHD5 may be a potential biomarker for the diagnosis and treatment of NOA (Han et al, 2021). However, the results of different reports do not match and the reason may be found in semen parameters, racial divisions and other gene interventions.…”
Section: Discussionmentioning
confidence: 99%
“…genes have the potential to become biomarkers Han et al in 2021. showed that CHD5 may be a potential biomarker for diagnosis and treatment of NOA(Han et al, 2021).…”
mentioning
confidence: 99%
“…In addition, from the perspective of pathogenesis, although many theories have been proposed to explain the pathogenesis of NOA, our understandings of the biological processes associated with NOA remains insufficient. Nowadays, the widespread applications of gene sequencing, especially scRNA-seq, have deepened the knowledge of NOA [ 25 , 26 ]. For instance, Wang et al had disclosed the unique role of autophagy homeostasis in the spermatogenesis of NOA cases through scRNA-seq analysis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%